2009
DOI: 10.1177/1358863x08096517
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular treatment of septic thrombophlebitis: a case report of a rare complication and review of the literature

Abstract: We report a case of severe deep venous thrombosis (DVT) treated with multimodality therapy that was complicated by sepsis due to thrombus likely infected by Salmonella virchow. We review the current therapeutic options in the therapy of severe DVT and cardiovascular pathology associated with non-typhoid Salmonella.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Volkow et al 3 used another thrombolysis agent (streptokinase) with an infusion rate ranging from 20 000 to 40 000 IU h −1 , using a bolus at the start of the thrombolysis (250 000 IU). This regimen was found to be successful in the treatment of 3 patients Schifferdecker et al 4 also reported better efficacy using in situ thrombolysis compared to general thrombolysis. This treatment regimen provides a combinatorial advantage as it removes both the thrombus and the source of infection while also lowering the thrombolysis agent dosage required, thereby reducing the risk of bleeding.…”
Section: Discussionmentioning
confidence: 94%
“…Volkow et al 3 used another thrombolysis agent (streptokinase) with an infusion rate ranging from 20 000 to 40 000 IU h −1 , using a bolus at the start of the thrombolysis (250 000 IU). This regimen was found to be successful in the treatment of 3 patients Schifferdecker et al 4 also reported better efficacy using in situ thrombolysis compared to general thrombolysis. This treatment regimen provides a combinatorial advantage as it removes both the thrombus and the source of infection while also lowering the thrombolysis agent dosage required, thereby reducing the risk of bleeding.…”
Section: Discussionmentioning
confidence: 94%
“…2) It has also been reported in patients with salmonella bacteremia secondary to osteomyelitis. 3,4) It is well recognized that intravenous drug abusers (IVDA) commonly present with skin or subcutaneous abscesses and suppurative thrombophlebitis of small veins. This often happens when attempting unsterile access to peripheral veins.…”
Section: Discussionmentioning
confidence: 99%
“…PE is one of the foremost causes of cardiovascular mortality, overtaken only by stroke and acute myocardial infarction [2]. The interplay between Salmonellae and the development of thrombosis has been known for more than a century, and subsequent studies have confirmed that acute infections are a risk factor for subsequent VTE [3][4][5][6][7][8]. Several animal models have shown the impact of bacterial infections on subsequent inflammation and coagulation in vivo.…”
Section: Introductionmentioning
confidence: 99%